2023
DOI: 10.1038/s41598-023-34030-0
|View full text |Cite
|
Sign up to set email alerts
|

Landslide detection and inventory updating using the time-series InSAR approach along the Karakoram Highway, Northern Pakistan

Abstract: Karakoram Highway (KKH) is frequently disrupted by geological hazards mainly landslides which pose a serious threat to its normal operation. Using documented inventory, optical imagery interpretation, and frequency-area statistics, the features of slope failure, the spatial distribution, and their link to numerous contributing factors have all been effectively explored along the KKH. An updated inventory for the area was recreated using the interferometric synthetic aperture radar (InSAR) persistent scatterer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The current study utilized RS techniques, such as optical RS and InSAR, for risk assessment and landslide mapping along the KKH [63,99,100]. This study took benefit of the multi-azimuth interpretation provided by the descending and ascending Sentinel-1 dataset, allowing for more extensive monitoring of surface displacement.…”
Section: Discussionmentioning
confidence: 99%
“…The current study utilized RS techniques, such as optical RS and InSAR, for risk assessment and landslide mapping along the KKH [63,99,100]. This study took benefit of the multi-azimuth interpretation provided by the descending and ascending Sentinel-1 dataset, allowing for more extensive monitoring of surface displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these maps quantify the limits of mass movements, determine statistical indexes for the frequency and spatial distribution of failures of a slope, and regress the consequences of particular landslide-triggering events, i.e., intense rainfall, rapid snowmelt, seismic activity, etc. [46] In this research, a landslide inventory was established utilizing visual image categorization techniques while employing SPOT-5 images. Additionally, field verification was conducted for the confirmation of identified landslides, and necessary adjustments were made.…”
Section: Landslide Inventorymentioning
confidence: 99%
“…Nava et al [37] identified landslides using attention U-Net and SAR data. Hussain et al [38] utilized InSAR time series for landslide detection and inventory update. Sentinel-1 data and InSAR technology were utilized by Dai et al [39] to detect active landslides.…”
Section: Introductionmentioning
confidence: 99%